The Effect of Cliteridetomie and Clitoral Coterizıation on Thyroxine, Cortosol and Testesterone Levels and Conception in Repeat Breeder Heifers. - Kalkan, Cahit; Timurkan, Hüseyin; Apaydın, Ali Mukremin; Ocal, Halis; Deveci, Hüseyin (Van Yüzüncü Yıl Üniversitesi, 1991)
In this study, 15 repeat breeder heifers were used.  Blood samples were taken from each animal during 2 destrus cycles. These animols were divided in to 3 groups. First group (A) was c1iteridectomized in the second oestrus. In the second group (B) the clitoral coterization was performed and third graup (C) was left as the control. All of heifers were inseminated in the third oestrus. The levels of thyroxine, cortisol and testosterone were measured by RIA in the blood serum samples. Cliteridectomie and clitoral coterization were found to be effecetive on conceptions of some repeat breeder heifers, but no statistically difference was found on the levels of thyroxine, cortisol and testosterone in the blood sera of these heifers.

Çalışmada, dol tutmayan 15 adet düve kullanıldı Her hayvandan iki östrus siklusu boyunca kan ornekleri alindi.  Bu hayvanlar  3 gruba ayrildi. 1. gruba (A), 2 östrusta, kliteridektomi; 2 gruba (B), klitorisin koterizasyonu uygulandı ve 3. grup (C) ise kontrol olarak tutuldu. Kan almaya son verilen 3. Ostruste, tüm duveler kontrollu olarak tohumlandı. Kan serumlarinda, RIA ile tiroksin (T4), kortozol ve testesteron miktarları ölçüldü. Dol tutmayan duvelerde, kliteridektomi ve klitorisin  koterizasyonu uygulaması, gebe kalmayı sağlamada bazı vakalarda etkili bulundu, fakat bu  uygulamanm kan serumu tiroksin, kortizol ve testesteron seviyeleri uzerinde istatistiksel anlamda herhangi bir değişiklik yapmadığı görüldü.
DÖL TUTMAYAN DÜVELERDE KLİTORİSİN ÇIKARILMASI VE KOTERİZASYONUNUN KAN TİROKSİN, KORTIZOL VE TESTESTERON SEVİYELERİ İLE GEBE KALMA ÜZERINE ETKİSİ